Rancang Bangun Aplikasi Operasional Departemen Finance Studi Kasus PT. Maja Kerta Wangi - Budiman, Budiman; Rakhman Alamsyah, Rd. Yadi; Fauzi Ramadhan, Ahmad (FKOM UNIKU, 2023)
The large number of travel document transactions, credit cards, and invoice payments is a problem that complicates the finance department. In actual work, many travel documents are printed more than once, which burdens printing costs, loads the capacity of archive space which must be stored for five years, and requires destroying documents whose expired shelf life. The verification and validation process carried out by officers experienced problems because the system had not been integrated, so travel documents became past due and caused delays in supplier payments. The design and construction of operational applications for the finance department aim to digitize and integrate operational and financial processes to become combined, especially in managing travel documents, debt cards, and bill payments. The software development method used in this study is the waterfall which consists of the stages of analysis, design, implementation, and testing. Based on the testing results, the application shows that the application can assist in the operational process of the financial section, especially the data collection of travel documents into debt cards, then processing and paying bills based on invoices.